Best approximation of periodic functions of several variables from the classes $MB^{ω}_{p,θ}$ - Stasyuk, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain exact-order estimates for the best approximation of periodic functions of several variables from the classes $MB^{ω}_{p,θ}$by trigonometric polynomials with the "numbers" of harmonics from graded hyperbolic crosses in the metric of the space $L_q$.